Richaud-Degert prime-producers - Mollin R.A.a; Goddard B. (Utilitas Mathematica, 1998)
We conclude the project of classifying all Euler-Rabinowitsch polynomials that generate maximal consecutive, distinct prime values for an initial range of input values. The discriminants of these polynomials turn out to be necessarily of Richaud-Degert type, namely those of the form n2 + r where r|4n.